(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2018)
Background: Information presented in society meetings has not been completely vetted through a formal review process. It is not entirely clear if it is accurate or will ever be published in peer reviewed journals. Materials and Methods: A Pubmed-Medline search was performed for all abstracts presented at the AHBPA from 2007-2009 Different variables including country of origin, study center, and academic institution were examined to determine if any could predict eventual publication. Results: 33.4% of all abstracts presented materialized into full text manuscripts. The average time to publication was 14 months. In total, 46% of abstracts were published in two journals, The Journal of the Hepato-Pancreateco-Biliary Association (26 %) and the Journal of Gastrointestinal Surgery (20%). Multi-centered studies had higher publication rates (39%) than single-centered studies (33%). Although domestic abstracts had higher publication rates (38%) than foreign abstracts (28%)and academic universities had higher publication rates (38%) than non-academic universities (28%) , none of the p-values reached statistical significance. None of the other variables studied were associated with publication. Conclusion: One third of all abstracts were eventually printed in peer reviewed journals. Presentations from multi-centered, domestic, and academic institutions are associated with a higher likelihood of publication, but were not statistically significant. Abstracts are most frequently featured in the journal of Hepato-Pancreateco-Biliary Association and Journal of Gastrointestinal Surgery. It is difficult to predict which posters will eventually be published. Clinicians should evaluate posters and oral presentations with a jaundiced eye, as only one third of them pass peer review.